Utilizing Stylistics for Advanced English Teaching: Linkages to Literature and Advertising - Rugaiyah Rugaiyah; Miranti Eka Putri; Andi Idayani; Muhammad Ilyas (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research is important in analyzing and describing language styles, which have become one of the linguistics categories. The use of language and language style in literary works has also been studied and is very important for linguistic and literary studies. This article illustrates that stylistic analysis is an effective method to help students improve their reading and appreciation skills. It begins by briefly reviewing how stylistics is applied to teaching English by researchers. It then discusses stylistic analysis and how to do it by providing some examples. Finally, it concludes that teaching advanced English should incorporate stylistics, which are both necessary and practical. Stylistics is one of the sub-topics of learning English in high schools. It can also help students understand advertising language. It also helps students learn foreign languages in English language teaching, such as Indonesian, by preparing them to learn and use foreign languages effectively. Furthermore, Students are expected to be able to understand the language of advertising. To understand the language of advertising, teachers must provide understanding to students through stylistics.